Learn History, think unity: National integration through History education in Cameroon, 1961-2018 (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Since independence, one of the greatest worries of African states has been how to maintain national cohesion amongst the multiplicity of ethnic groups which characterize them. My aim in this paper is to show that, other factors notwithstanding, national integration had been a major educational ideology in Cameroon and that it contributed to the peace and stability that the country was known for, amidst a turbulent central African region until the advent of neoliberalism and multiparty politics in 1990. I discuss the nature of contents that helped to achieve this while arguing that a de-emphasis on the social sciences and particularly on the integrationist approach to history education in the multiparty era is not unconnected to the post-1990 reinvention of various parochial identities antithetic to national cohesion in which recent calls for the secession of the Anglophone region by some radical groups is seen as the culmination of the trend. I conclude by highlighting the social relevance of curriculum within which history education should be re-invented as a vector for peace, unity and national integration in the country.
Keywords: History Curriculum; Cameroon History; Peaceful Co-existence; National Unity; National Integration